CHL Calabi-Yau threefolds: curve counting, Mathieu moonshine and Siegel modular forms - Bryan, Jim; Oberdieck, Georg (Communications in number theory and physics, 2020)
International Press of Boston - publishers of scholarly mathematical and scientific journals and books